The impact of activity-based interventions on neuropathic pain in experimental spinal cord injury - Chen, Jing; Weidner, Norbert; Puttagunta, Radhika (Cells, 2022)
Physical activity-based rehabilitative interventions represent the main treatment concept for people suffering from spinal cord injury (SCI). The role such interventions play in the relief of neuropathic pain (NP) states is emerging, along with underlying mechanisms resulting in SCI-induced NP (SCI-NP). Animal models have been used to investigate the benefits of activity-based interventions (ABI), such as treadmill training, wheel running, walking, swimming, and bipedal standing. These activity-based paradigms have been shown to modulate inflammatory-related alterations as well as induce functional and structural changes in the spinal cord gray matter circuitry correlated with pain behaviors. Thus far, the research available provides an incomplete picture of the cellular and molecular pathways involved in this beneficial effect. Continued research is essential for understanding how such interventions benefit SCI patients suffering from NP and allow the development of individualized rehabilitative therapies. This article reviews preclinical studies on this specific topic, goes over mechanisms involved in SCI-NP in relation to ABI, and then discusses the effectiveness of different activity-based paradigms as they relate to different forms, intensity, initiation times, and duration of ABI. This article also summarizes the mechanisms of respective interventions to ameliorate NP after SCI and provides suggestions for future research directions.